Pavement properties of asphalt modified with packaging‐waste polyethylene. Issue 1 (6th February 2014) - Fang, Changqing; Wu, Caixia; Hu, Jingbo; Yu, Ruien; Zhang, Zengping; Nie, Long; Zhou, Shisheng; Mi, Xinghua
<x xml:space="preserve">Abstract</x> Recycled packaging‐waste polyethylene (WPE) was used to replace the ordinary polymer modifier in the modification of raw asphalt, and the pavement properties of the modified asphalt were studied. The high‐temperature stability, anti‐cracking properties at low temperature, life span, and stability against water of the asphalt mixture were improved, a finding which is attributed to the properties and characteristics of WPE, the swelling of sheared WPE, and the WPE/asphalt network structure. The use of packaging WPE can improve the pavement properties of asphalt, as well as save resources and reduce white pollution. J. VINYL ADDIT. TECHNOL., 20:31–35, 2014. © 2014 Society of Plastics Engineers